New approach of blending polymeric ionic liquid with polybenzimidazole (PBI) for enhancing physical and electrochemical properties - Rewar, Anita S.; Chaudhari, Harshal D.; Illathvalappil, Rajith; Sreekumar, K.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
Although the use of ionic liquids (IL) in polymeric membranes is known to elevate the electrochemical performance for proton exchange membrane-based fuel cells (PEMFC), they suffer from drawbacks such as IL drain and lowering in mechanical properties that lead to deterioration in PEMFC performance. To mitigate these issues, we report, for the first time, the use of polymeric ionic liquid (PIL), namely, poly(diallyl dimethyl ammonium trifluoride methane sulphonate) (P[DADMA][TFMS]) to be blended with polybenzimidazole (PBI-I) as a membrane material for PEMFC. PBI-I and (P[DADMA][TFMS]) were chosen because they form miscible blends and are suitable for acid doping as a matrix, which can eventually be used as proton conductor. The structure, miscibility and inter-polymer interactions were studied by infrared (IR) spectroscopy and differential scanning calorimetry (DSC). The increase in proton conduction in comparison to the PBI membranes was observed due to the presence of ionic groups of PILs in blend membranes. With the increase in PIL content, the proton conductivity of the composite membranes gradually increased from 0.04 S cm(-1) for PBI to 0.07 S cm(-1) for the blend membrane at 150 degrees C. The MEAs were fabricated with PBI-I, PBI-PIL15, PBI-PIL25 and PBI-PIL35. Corresponding single cells were successfully tested at temperatures of 160 degrees C. The maximum power density and current density obtained were 515 mW cm(-2) and 1632 mA cm(-2), respectively, for PBI-PIL25-based MEA.